Effectivity of borate micro fertilizer on yield of cucumber (Cucumis sativus L.) - Suwarto, Suwarto; Hilmi, Muhammad; Hapsari, Dhika Prita (Department of Agronomy and Horticulture, IPB University, 2024)
Boron (B) is one of the most essential nutrients for fertilization and the production of fruits and seeds, however the availability of boron in soil is very limited. The aim for this experiment is to test the borate micro fertilizer to improve the growth and production of cucumber (Cucumis sativus). The fertilizer used in this experiment is borate micro fertilizer which contain 46% or 460 g.kg-1 B2O3. The experiment was conducted at Cibadak Village, Sukaresmi District, Cianjur Regency, West Java Province. Treatments in this experiment were arranged within five rates of fertilizer, which are: without fertilizer (P0); 0.5 rate of Borate fertilizer (0.5 B) (P1); 1.0 rate of Borate fertilizer (1.0 B) (P2); 1.5 rate of Borate fertilizer (1.5 B) (P3); and 2.0 rate of Borate fertilizer (2.0 B) (P4). The result showed that the treatment of 0.5 to 2.0 rate of borate micro fertilizer can produce growth characteristics and plants that are better compared to the control treatment. Applicating 0.5 rate of borate micro fertilizer even has the capacity of yielding production up to 48.960 kg.ha-1. The 0.5 rate of Borate micro fertilizer treatment was concluded as the most effective one compared to other treatments, due to its capacity to produce the highest relative agronomical effectivity value, which is 152%. The recommended rate of Borate fertilizer is 25 kg.ha-1 given by soil drench at 15 and 30 DAP (days after planting) with the concentration is 1.5 g.L-1 and the volume is 250 ml/plant.